Controlling Chaos and Voltage Collapse using Layered Recurrent Network-based PID-SVC in Power Systems - I Made Ginarsa; Agung Budi Muljono; I Made Ari Nrartha (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Chaos and voltage collapse occurred in critical power systems due to disturbing of energy. PID-SVC layered reccurrent neural network-based (LRN-based PID-SVC) was proposed to solve these problems. The PID is used to control chaos and voltage collapse. Meanwhile, an SVC LRN-based is used to maintan the load voltage. By using the proposed controller, chaos and voltage collapse are able to suppress and maintain the load voltage around the setting value. When the maximum load isforced to load bus, the reactive power supplied by SVC, SVC additional voltage and load voltage are at the values of j0.1127, 4.0095´10-3 and 0.980010 pu, respectively. Furthemore, the proposed controller gives better response than PI-SVC controller.